2010
DOI: 10.1007/s10643-010-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Picture Partners: A Co-creative Journey into Visual Literacy

Abstract: This article describes an integrated art and early literacy project entitled, 'Picture Partners'. The main purpose of the project was to explore how young children create and express meaning through art. Children's responses, both written and spoken, were included because accompanying modes of expression expand the nature and content of their drawings and inform teachers about children's intentions and processes of thinking. A secondary purpose was to investigate how children use illustrations from familiar pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…It is interesting to note that when the teachers in Mischa's school were shown the various examples of digital art-making created by children in the class, they showed particular admiration of Mischa's artwork, declaring it to be an example of 'mature use' of the media (see Author, 2013). This highlights the common perception in early years education that children's art-making is a journey towards visual realism (Soundy & Drucker, 2010), which Mischa's artmakingincluding the particularly careful use of the ready-made imagerepresents a step towards.…”
Section: Gertrude: Image Use Is the Basis For The Development Of Narrmentioning
confidence: 80%
See 1 more Smart Citation
“…It is interesting to note that when the teachers in Mischa's school were shown the various examples of digital art-making created by children in the class, they showed particular admiration of Mischa's artwork, declaring it to be an example of 'mature use' of the media (see Author, 2013). This highlights the common perception in early years education that children's art-making is a journey towards visual realism (Soundy & Drucker, 2010), which Mischa's artmakingincluding the particularly careful use of the ready-made imagerepresents a step towards.…”
Section: Gertrude: Image Use Is the Basis For The Development Of Narrmentioning
confidence: 80%
“…Supporting children to be playful in their use of ready-made images relies on adults accepting the 'multiple pathways' that children can take when making art (Duncum, 1999;Louis, 2013). As suggested by the teachers' admiration of Mischa's digital artwork (figure 6), early years education tends to posit visual realism as the desirable and singular endpoint of art education (Soundy & Drucker, 2010). McRae (2011) discusses a tendency of early years teachers to assume and celebrate 'a coherent and unifying representational thread that gives the work meaning' (p. 103).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that storytelling in art-making is not exclusive to digital resources, and it has been observed in the context of children's non-digital art-making in multiple studies (Kolbe, 2005;Anning, 2002Anning, , 2003MacRae, 2011). Previous research has also found however, that early years practitioners tend to value children's art-making when it involves discernible representations (Soundy & Drucker, 2010;Duncum, 1999). Digital resources, as a result of the limited adult guidance and intervention they are typically associated with, may foreground the potential for art-making to manifest as performance and play since there is more space for the 'heterogeneous, dissonant and absurd' (Tam, 2012, p. 251).…”
Section: Is It Another Jelly Flood?mentioning
confidence: 99%
“…While this might be a popular conception of art-making among adults working in the early years (Labbo, 1996;Soundy & Drucker, 2010;Duncum, 1999), it was a relatively unpopular approach to take among the children in the class. Had Levi as the class's first 'expert' put forward or enacted this form of digital art-making, it might have been much more popular over the course of the week.…”
Section: Attributing 'Expert' Statusmentioning
confidence: 99%
“…Storybooks with images enable children to learn about the real world, especially those aspects that they have not experienced directly (Woolley & Cox, 2007). Photographic images in narrative are particularly valuable as they support oral and written explanations, add depth to the child's understanding, promote discussion of complex concepts, depict ideas that are not easily articulated (Ruiz-Casares & Thompson, 2014), and stimulate children's visual thinking (Soundy & Drucker, 2010).…”
Section: An Interactive Narrative Approach To Informing Young Childrenmentioning
confidence: 99%